Investigation of the EMG-Time Relationship of the Biceps Brachii Muscle During Contractions - Ahamed, Nizam Uddin; Ahmed, Nasim; Alqahtani, Mahdi; Altwijri, Omar; Ahmad, Badlishah; Sundaraj, Kenneth (The Society of Physical Therapy Science, 2015)
[Purpose] This study investigated the changes in the slope of EMG-time curves (relationship) at the maximal and different levels of dynamic (eccentric and concentric) and static (isometric) contractions. [Subjects and Methods] The subject was a 17 year-old male adolescent. The surface EMG signal of the dominant arm’s biceps brachii (BB) was recorded through electrodes placed on the muscle belly. [Results] The results obtained during the contractions show that the regression slope was very close to 1.00 during concentric contraction, whereas those of eccentric and isometric contractions were lower. Significant differences were found for the EMG amplitude and time lags among the contractions. [Conclusion] The results show that the EMG signal of the BB varies among the three modes of contraction and the relationship of the EMG amplitude with a time lag gives the best fit during concentric contraction.